WASIAT KEPADA WARIS: PEMBAHARUAN UNDANGUNDANG DAN PENGGUBALAN DI SELANGOR, MALAYSIA - Sulong, Jasni (Jurnal Syariah, 2019)
The rigidity of the law previously applicable to bequest has been partially relaxed in some of Muslim Countries. The limit of a testator to make any bequest in favour of a legal heir and subject to the consent of all the other heirs after his demise has been abolished and reformed in Egypt, Sudan and Iraq. Hence, the modern law was promulgated and allows a bequest in favour of an heir within bequethable third. This relaxation shows that the fiqh of bequest is dynamic from the past hitherto. Therefore, this article analyzes the change from shariah perspective and its application in Malaysia.